Economic study of four agroforestry models with cocoa crop in Brazilian Amazonia - Teixeria, F (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica), 2021)
4 tablas, 7 ref.